2017
DOI: 10.15446/agron.colomb.v35n2.59973
|View full text |Cite
|
Sign up to set email alerts
|

Variability and genetic structure of yellow passion fruit (Passiflora edulis f. flavicarpa Degener) in Colombia using microsatellite DNA markers

Abstract: Colombia is one of the leading producers of yellow passion fruit but the genetic studies based on molecular markers from commercial plantations have not been considered to select interesting market material. The goal of this study was to assess the genetic variability and the population structure of 51 Colombian commercial yellow passion fruit accessions (102 individuals), and to provide the necessary information for prospective selection and breeding programs. Thus, a total of six microsatellites were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 49 publications
2
10
0
1
Order By: Relevance
“…The average value of Nei-Li genetic diversity was 0.40, consistent with that expected for cross-pollinated species and with the values observed in studies on genetic diversity in Passiflora (Santos et al, 2011;Oluoch et al, 2018;Oliveira et al, 2019;Vianna et al, 2019). Ocampo et al (2017), when evaluating the diversity and genetic structure of P. edulis f. flavicarpa in Colombia with microsatellites, found an average genetic distance of 0.683 and that the structuring of the groups was not consolidated and could vary, just as in this study it was observed that the internal branches of the dendrogram were moderately compatible (bootstrap ≥ 50%) and ratified the grouping between some materials of the same department. The relationship between individuals of the same species was low and did not present a geographical pattern according to the origin of each material.…”
Section: Meneses Et Al 2019)supporting
confidence: 87%
See 4 more Smart Citations
“…The average value of Nei-Li genetic diversity was 0.40, consistent with that expected for cross-pollinated species and with the values observed in studies on genetic diversity in Passiflora (Santos et al, 2011;Oluoch et al, 2018;Oliveira et al, 2019;Vianna et al, 2019). Ocampo et al (2017), when evaluating the diversity and genetic structure of P. edulis f. flavicarpa in Colombia with microsatellites, found an average genetic distance of 0.683 and that the structuring of the groups was not consolidated and could vary, just as in this study it was observed that the internal branches of the dendrogram were moderately compatible (bootstrap ≥ 50%) and ratified the grouping between some materials of the same department. The relationship between individuals of the same species was low and did not present a geographical pattern according to the origin of each material.…”
Section: Meneses Et Al 2019)supporting
confidence: 87%
“…The AMOVA showed that 64% of the variation observed in the evaluated Passiflora materials was explained by the component within the groups, and 36% was explained by the differentiation between the groups, so it is necessary to consider subdivision levels and hierarchy greater than those contemplated in this study, in addition to the high levels of variation at the intraspecific level, which should be used for management and conservation strategies of this plant genetic resource (Table 4), which has also been reported in other genetic diversity studies on Passiflora using this marker (Ocampo et al, 2017;Oluoch et al, 2018;Fonseca-Trujillo et al, 2019). In interspecific analyses, a higher polymorphism rate in combination with a higher average number of bands amplified per primer is indicative of high genetic diversity (Cerqueira-Silva et al, 2012).…”
Section: Meneses Et Al 2019)mentioning
confidence: 64%
See 3 more Smart Citations